Novel morphological classification of the normal pancreatic uncinate process based on computed tomography. Issue 9 (September 2020) - Zhu, Chunfu; Ma, Le; Jia, Zhongzhi; Shi, Haifeng; Jin, Jianliang; Lou, Wenhui; Qin, Xihu
Objectives: This study aimed to assess computed tomographic (CT) features of the normal pancreatic uncinate process (UP) and to classify UP types on the basis of morphological characteristics. Methods: From November 2017 to December 2018, consecutive Han Chinese adults were enrolled in this retrospective study. Morphometric evaluation of the UP was performed using CT imaging, including assessment of the maximal transverse diameter of the UP (MTDUP) and pancreas head, and assessment of the relationship between the UP and superior mesenteric vessels. Results: A total of 318 participants were studied. The mean MTDUP and maximal transverse diameter of the pancreas head were 15.89 ± 4.82 mm and 46.47 ± 7.18 mm, respectively. The mean MTDUP was 10.83 ± 2.59 mm for type I UP (21.70% of participants), 13.87 ± 2.35 mm for type II (13.21%), 17.08 ± 3.43 mm for type III (56.29%), and 23.74 ± 5.02 mm for type IV (8.81%). There was a significant difference among the UP types. Conclusions: Four types of normal UP can be defined on the basis of morphological CT features. The length of the UP significantly increases from types I to IV, and type III accounts for > 50%.